2021
DOI: 10.1515/jbnst-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Working from Home, Wages, and Regional Inequality in the Light of COVID-19

Abstract: We use the most recent wave of the German Qualifications and Career Survey to reveal a substantial wage premium in a Mincer regression for workers performing their job from home. The premium accounts for more than 10% and persists within narrowly defined jobs as well as after controlling for workplace characteristics. In a next step, we provide evidence on substantial regional variation in the share of jobs that can be done from home in Germany. Our analysis reveals a strong, positive relation between the shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 27 publications
1
28
0
2
Order By: Relevance
“…In addition, one more important control measure is school closure, which has been massively criticized in Africa since many countries on the continent spontaneously closed down schools with the absence of exhaustive e-learning systems and inadequate infrastructure, as has been practiced in many other countries (22). Some of the main challenges regarding the fight against the COVID-19 pandemic in Africa include the imposition of the hand-hygiene policy when the majority of Africans do not have access to an adequate and portable water supply, temperature screening at airports for travelers without considering asymptomatic carriers (asymptomatically infected people), the impossibility of work from home policies, and an insufficient quantity of PPEs, especially for frontline health workers, insufficient data sharing, and illegal crossing of borders at non-official points of entry (2,(26)(27)(28)50).…”
Section: Discussion: the Implementation And Implications Of Npismentioning
confidence: 99%
“…In addition, one more important control measure is school closure, which has been massively criticized in Africa since many countries on the continent spontaneously closed down schools with the absence of exhaustive e-learning systems and inadequate infrastructure, as has been practiced in many other countries (22). Some of the main challenges regarding the fight against the COVID-19 pandemic in Africa include the imposition of the hand-hygiene policy when the majority of Africans do not have access to an adequate and portable water supply, temperature screening at airports for travelers without considering asymptomatic carriers (asymptomatically infected people), the impossibility of work from home policies, and an insufficient quantity of PPEs, especially for frontline health workers, insufficient data sharing, and illegal crossing of borders at non-official points of entry (2,(26)(27)(28)50).…”
Section: Discussion: the Implementation And Implications Of Npismentioning
confidence: 99%
“…In the UK, being able to work from home was correlated with higher education, higher income, more savings, and people who own their own houses (Atchison et al, 2020). In general, workers that cannot work from home tended to be lower paid than workers who can work from home (Atchison et al, 2020;Baker, 2020;Dingel & Neiman, 2020;Irlacher & Koch, 2020;. In other words, most research on this topic focused on income, education, and occupation type as explanatory variables and demonstrated that people who were already disadvantaged were less able to comply with preventive measures such as social distancing, stayat-home, or shelter-in-place policies.…”
Section: Work From Homementioning
confidence: 99%
“…The geographical and social context is crucial with urban areas having a higher ratio of WFH positions than rural areas, and vulnerable parts of the society (i.e., migrants, single parents, low qualified workers) have less likelihood to get such jobs [10]. A lower share of jobs with the WFH options is found in East Germany and a much higher share in urban areas, such as, Berlin, Darmstadt, Hamburg and Munich [11]. Analysis of data from several countries has shown that richer and more developed countries have had a higher number of jobs that can be run from home [10], whereas in regions with a low share of WFH jobs, a lower average income has been observed [11].…”
Section: Literature Review: Wfh During the Covid-19 Pandemicmentioning
confidence: 99%
“…A lower share of jobs with the WFH options is found in East Germany and a much higher share in urban areas, such as, Berlin, Darmstadt, Hamburg and Munich [11]. Analysis of data from several countries has shown that richer and more developed countries have had a higher number of jobs that can be run from home [10], whereas in regions with a low share of WFH jobs, a lower average income has been observed [11].…”
Section: Literature Review: Wfh During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation